Υπολογιστές υψηλής επίδοσης (HPC) για αντίστροφα προβλήματα: Εφαρμογή στην επιτήρηση δομικής αντοχής πλοίων - Μπάκαλος, Νικόλαος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ηλεκτρολόγων Μηχανικών και Μηχανικών Υπολογιστών. Τομέας Επικοινωνιών, Ηλεκτρονικής και Συστημάτων Πληροφορικής, 2017)
Risk assessment engineering for vessels is currently undergoing a “perfect storm”. Namely: a convergence of immense amounts of sensor data, new supercomputers (High Performance Computing -HPC) to analyse it, and improved mathematical models to plug the data into. All of these converging streams have to funnel through a bottleneck known as inverse problems. Without fundamental improvements in this essentially computational problem, we will lose much of the opportunity for extracting knowledge from the data deluge. Computational Inverse Problems can drive a Big Data revolution. The combination of computer science applied mathematics and continuum mechanics are necessary to solve the problems together with advanced statistical and stochastic methods. Consider an ocean travelling big vessel, tanker or container-ship, which has a full array of sensors on many positions of its hull, as well as other measuring devices measuring and keeping data on sea waves, wind speed, geographic location, and time. We can collect all these data almost continuously in time. We would like to use the full stress and strain fields and the hydrodynamic partial differential equations (PDE’s) describing the interaction of the sea waves and the wind with vessel, taking data from all the instruments and integrating them through an inverse problem. Our aim is to solve the distribution of elastic properties inside the hull of the vessel and isolate the points of high fatigue and high corrosion at which there is a grave risk to have the beginn ing of a serious damage, by providing an information system that will alert for one or a worldwide fleet of vessels for such incidents, and preventing damages and pollution with impact in human life and in oceans and in our earth environment.